Development of Rutting Performance Model for Recycled Hot Mix Asphalt with Bioasphalt using Hamburg Wheel Tracking Device - SUBAGIO, Bambang Sugeng; SIHOMBING, Atmy Verani Rouly; IMANUEL, Ivan (Journal of the Eastern Asia Society for Transportation Studies, 2024)
Rutting is an important problem related to road asphalt pavement distress. The use of Reclaimed Asphalt Pavement (RAP) has been one of the alternatives to improve the rutting performance of asphalt. Bioasphalt can be used to rejuvenate the quality of aged bitumen in RAP. This research aims to measure the rutting performance of hot mix asphalt containing RAP and Bioasphalt Bitutech RAP (BioBT) and bioasphalt coconut shell (BioCS) using Hamburg Wheel Tracking Device. The results show mixtures with BioCS have better rutting resistance than those with BioBT. Preliminary rutting models obtained however indicate mixtures with BioBT have stronger correlation to RAP content in mixture. The higher the RAP content is, the lower rutting resistance BioBT mixtures have. On the other hand, rutting resistance of BioCS mixtures at 45°C is increased with the addition of RAP.